Evaluation of the traffic performance measure for exclusive motorcycle lane at merging section / Tuan Badrol Hisham Tuan Besar, Mohammad Akmal Suhaimi and Muhammad Akram - Tuan Besar, Tuan Badrol Hisham; Suhaimi, Mohamad Akmal; Akram, Muhamad (Universiti Teknologi MARA Cawangan Selangor, 2017)
Exclusive Motorcycle Lane (EML) is defined as a roadway meant exclusively for motorcycles or can be stated as motorcyclists who are compelled by law to use it and other vehicles are prohibited by law from using it. It is physically separated from the mainstreams carriageway and is grade separated from the main carriageway at intersections, interchanges or points of conflicts. Merging is one of the parts of way that motorcycle deceleration the speed from main stream lane to enter the Exclusive Motorcycle Lane (EML) with safe. The urban expressways in Malaysia have serious problems regarding the safety, efficiency and comfort ability at merging sections of an EML because of the insufficient geometric due to limited land and the right of way design configuration condition. The increase of traffic volume and demand lead towards the degradation of motorcyclist performance while on their wheels. This research is performed in order to achieve the objectives, i.e. to obtain and analyze local empirical data, such as flow rate, headway and speed on exclusive motorcycle lane at merging section that reflects on the local traffic condition on Federal Highway Route 2, and to obtain regression modeling that relates to Flow Rate with regards to the Headway 1-3, Time Mean Speed and Length of Merging Ramp section, Lm on the merging section of EML and merging ramp section. Two regression models have successfully been performed with R-Sq 94.8 % for EML section and 31.1 % for merging ramp section. Its also highlighted the attributes of EML.